TINJAUAN BENTUK PERTANGGUNGJAWABAN PT TOKOPEDIA SELAKU MARKETPLACE DALAM RANGKA MENYEDIAKAN SISTEM ELEKTRONIK YANG ANDAL DAN AMAN BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK JO. UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Samuel Evan; Christine S.T. Kansil (Jurnal Hukum Adigama, 2020)
Everyone should already know about legal responsibility. Legal responsibility itself takes many forms. Problems arise when a regulation, especially a law, does not clearly explain the form or principle of legal responsibility that applies in the application of the regulation. This is clearly seen in Article 15 of the ITE Law, where it does not state what forms of legal responsibility can be applied to electronic system administrators in the operation of the electronic system. Determining the form of legal responsibility in the ITE Law is very important considering the rapid growth of electronic transactions (e-commerce) both in the world and in Indonesia. The development of e-commerce has certainly led to an increasing number of companies engaged in e-commerce. PT Tokopedia as one of the largest marketplaces in Indonesia is a testament to the rapid development of e-commerce. In running its business, PT Tokopedia is bound to and must comply with the ITE Law as part of the electronic system organizer. As a result of unclear regulations regarding the legal responsibility of electronic system administrators in the ITE Law, it can cause injustice to the community, especially as users of electronic system services. There is a need for clearer regulations regarding the form of legal responsibility for administrators of this electronic system in order to achieve legal certainty and also justice for all parties in e-commerce activities.